« L’Univers Illustré » de La Presse: The Animation of Newspaper Pages in Late 19th Century - Moore, Paul; Gabriele, Sandra (Nouvelles vues)

(untitled) (Observatoire du cinéma au Québec, 2013)
In the late 1890s, all media were striving for the same aims of technological reproducibility : immediacy, imaginative association, and bridging located temporality through communication and amusement. This essay considers newspapers as part of that milieu, reversing the idea that early cinema emulated a "visual newspaper." Journalism itself was becoming visual in the 1890s, following a "cinematic" ideal. In Quebec, this is most apparent in La Presse, especially its weekly feature L'Univers Illustré (1897-1898), which depicted a montage of newsworthy events in picture form. By introducing illustrations, colour printing, and even experimenting with Sunday editions, La Presse played a key role in transforming newspaper reading in Quebec into a popular pastime, in parallel and concurrent with the emergence of cinema.